P097: Evaluation of an oral morphine protocol for treatment of acute pain crisis in sickle cell patients in the outpatient setting. (2nd June 2016) - Paquin, H.; Trottier, E.D.; Pastore, Y.; Robitaille, N.; Dore Bergeron, M.; Bailey, B.
Abstract : Introduction: Sickle cell vaso-occlusive crisis (VOC) is one of the most frequent causes of emergency visit and admission in children with this condition. With this study, we aim to evaluate whether the implementation of an oral morphine protocol has led to improved care of sickle cell disease (SCD), translated by a reduced hospitalization rate, an increased oral administration rate and faster opiate administration time, comparing cohorts of patients presenting to the emergency department (ED) and hematology outpatient clinic (HOC) with VOC pre and post implementation.Methods: Retrospective chart review of patients with SCD followed at CHU Ste-Justine, who presented to the ED and HOC with VOC, in the year pre and post implementation of the protocol. Patients with a VOC diagnosis during the study periods were selected in each department's database. The primary outcome was to evaluate the hospitalization rate. The rate of oral administration, as well as the opiate administration time from inscription in the ED or arrival in the HOC were also calculated. We estimated that 35 patients per arm would be sufficiently powered to detect at least a 30% rate reduction of admissions, with a power of 80% and a significance of 0.05.Results: Over the two periods, a total of 105 patients (49 pre and 56 post) were included from the ED and 62 patients (36 pre and 26 post) from the HOC. Both departments showed a reduction in hospitalization rate: a difference of 48% (95% CI 32, 61) in ED and 38% (95% CI 13, 57) in HOC. Both showed an increase in the rate of oral administration: a difference of 36% (95% CI 19, 50) in ED and 33% (95% CI 8, 53) in HOC. There was a non-significant difference of 10 min (95% CI -10, 25) in the opiate administration time in ED, as opposed to HOC where a significant difference of -45 min (95% CI -71, -6) was found, with both presenting median times over the recommended 60 minutes post implementation. Both settings showed an increase in the percentage of patients without IVs; a difference of 17% (95% CI 4, 30) in ED and 55% (95% CI 72, 31) in HOC.Conclusion: This study validates the use of our oral morphine protocol for the treatment of VOC, by showing a significant reduction in hospitalization rates. Although delays remain in our opiate administration time, our protocol decreased the number of painful IV procedures.